Ultrasonic irradiation of activated industrial sludge. (11th October 2010) - Singh, Manoj Kumar; Kesari, Kavindra Kumar; Behari, Jitendra
Sludge is a by-product of wastewater treatment and contains multitude of pollutants. In the present study, irradiation with ultrasound as treatment technique was carried out to treat complex effluent paper sludge, sugar sludge and sewage sludge samples from different industrial places. Wastewater samples were treated in ultrasonic bath at 25 kHz for different time periods of 5 min, 10 min, 20 min and 30 min. Treated wastewater samples were tested for different parameters, viz. particle size reduction by particle size analyser, chemical oxygen demand (COD), degree of disintegration COD, ammonical nitrogen and total phosphorus. Results show that the extent of disintegration by ultrasonication in wastewater samples was different in the three cases. Sewage sludge had maximum disintegration followed by paper and sugar sludge. It is concluded that low-frequency ultrasonication is very effective in decreasing the bacterial population in industrial wastewater samples.